Sociodemographic, clinical, and functional long‐term outcomes in adolescents and young adults with mental disorders. (31st August 2017) - Asselmann, E.; Wittchen, H.‐U.; Lieb, R.; Beesdo‐Baum, K.
Abstract : Objective: To examine unfavorable sociodemographic, clinical, and functional long‐term outcomes for a range of adolescent mental disorders. Methods: A total number of 2210 adolescents and young adults (14–24 years at baseline, T0) from a representative community sample were prospectively followed up (T1–T3) over 10 years. DSM‐IV mental disorders, sociodemographic, clinical, and functional outcomes were assessed using the DIA‐X/M‐CIDI and its embedded assessment modules. Results: In (multinomial) logistic regressions adjusted for sex, age, other baseline disorders and sociodemographics, baseline anxiety, affective, substance use, somatoform and eating disorders (lifetime) predicted various unfavorable sociodemographic, clinical, and functional outcomes at T3. Particularly, strong associations were found between baseline disorders and adverse clinical outcomes at T3 (12‐month diagnosis of the same/other disorder(s), drug use, suicide attempts, and help‐seeking due to psychological problems). While substance use disorders were primarily associated with unfavorable sociodemographic and educational outcomes, anxiety and eating disorders were associated with unfavorable interpersonal outcomes, affective disorders with pregnancy‐/childbirth‐related complications and financial issues, and somatoform disorders with unfavorable educational/occupational and interpersonal outcomes. The risk of unfavorable outcomes increased with clinical severity, especially a higher number of baseline diagnoses. Conclusions: Our findings emphasize the importance of effective treatment of mental disorders to prevent unfavorable long‐term outcomes in various life domains.